1998
DOI: 10.1046/j.1365-2044.1998.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Revised checklist for anaesthetic machines

Abstract: SummaryA revised edition of the guidelines of the Association of Anaesthetists of Great Britain and Ireland, for the pre-operative check of anaesthetic machines, was published in March 1997. A checklist based on the revised guidelines was used for the routine pre-operative checks of anaesthetic machines over a 6-week period in a district general hospital. One hundred and thirty-two checklists were completed. These were analysed for the time taken to complete the check and for the faults found in the anaestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Anaesthesia checklists to prevent machinery problems appeared more than a decade ago. Studies showed that various checklist concepts detected machinery faults in 50- [4][5][6]. The lists or protocols varied between hospitals vary and it was not clear whether some hospitals ever used these lists.…”
Section: Discussionmentioning
confidence: 99%
“…Anaesthesia checklists to prevent machinery problems appeared more than a decade ago. Studies showed that various checklist concepts detected machinery faults in 50- [4][5][6]. The lists or protocols varied between hospitals vary and it was not clear whether some hospitals ever used these lists.…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of a checklist for the preoperative check of anesthetic machines in 1990, 29,30 there has been concern about widespread failure to perform adequate preoperative checks of anesthetic machines. This is despite most anesthesiologists' being aware of the guidelines and of the importance of checking anesthetic equipment before use.…”
Section: Discussionmentioning
confidence: 99%
“…Kendall et al showed that in 60 -82.5% of machines checked, at least one fault was present, of which 11-18% were deemed serious. 29,30 Several authors have suggested that the most important reason for failure to follow the guidelines is that they are perceived as to time consuming. [31][32][33] Therefore, the equipment checks and their guidelines must be a compromise between safety and practicability.…”
Section: Discussionmentioning
confidence: 99%
“…Kendell and Barthram [26] observed the implementation of a safety checklist for anesthesia equipment based on revised guidelines. The observation, conducted in a district general hospital for 6 weeks, resulted in the completion of 132 checklists.…”
Section: Checklist Use In the Operating Roommentioning
confidence: 99%